Outcome of Transcutaneous Electrical Nerve Stimulation (TENS) device for patients with chronic non-specific low back pain (Bangladesh Critical Care Journal, 2022)
Background : Transcutaneous electrical nerve stimulation (TENS) was introduced more than 30 years ago as an adjunct to the pharmacological management of pain.Objective : This controlled trial examined the benefit of TENS on patients with chronic non-specific low back pain.Methods : This randomized controlled clinical trial was conducted in the department of Physical Medicine and Rehabilitation of Bangabandhu Sheikh Mujib Medical University, Dhaka over a period of 6 months from March,2013 to August,2013. One hundred and ten (n=110) participants were treated. 55 patients were treated with NSAID+ADL, consider as Group-A (treatment as usual control group) and 55 patients were treated with NSAID+ADL+TENS, consider as Group-B (experimental group).Result : The mean age was found 39.1 ± 1.34 years in Group-A and 41.3 ± 2.80 years in Group-B.. Mean duration of pain was found 23.20 ± 2.34 months in Group-A and 21.00 ± 1.50 months in Group-B. Subjective pain intensity, Visual analogue score, tenderness index improved in both groups after at the end of 3rd week and at the end of 6th week, which was statistically significant but in between two groups there is no statistically significant difference.Conclusion :These results suggested that TENS specifically could not have an effect in reducing pain and improving quality of life in chronic non specific low back pain patients but as number of patients were small no firm conclusion could be drawn.Bangladesh Crit Care J March 2022; 10 (1): 26-32